2010
DOI: 10.4049/jimmunol.1000756
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Dampens Host Defense by Downregulating IL-17 Production

Abstract: IL-17 is one of the key cytokines that stimulate host defense during a Candida infection. Several studies have demonstrated the capacity of Candida albicans to induce a Th17 response. Surprisingly, experiments employing live C. ablicans demonstrated a specific downregulation of host IL-17 secretion in human blood mononuclear cells (PBMCs). By avoiding the direct contact of live C. albicans and PBMCs, we demonstrate that this inhibition effect is mediated by a soluble factor released by live C. albicans. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…Five-hydroxytryptophan metabolites inhibit IL-17 production. 193 Thus, live C. albicans may inhibit host Th17 responses, and experiments using live C. albicans, heat-killed C. albicans or PAMPs may lead to different conclusions. Secondly, more in-vivo research data are needed to better understand oral/vaginal candidiasis and host immune responses.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
See 2 more Smart Citations
“…Five-hydroxytryptophan metabolites inhibit IL-17 production. 193 Thus, live C. albicans may inhibit host Th17 responses, and experiments using live C. albicans, heat-killed C. albicans or PAMPs may lead to different conclusions. Secondly, more in-vivo research data are needed to better understand oral/vaginal candidiasis and host immune responses.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
“…One more example is that live C. albicans and heat-killed C. albicans may lead to different Th17 responses. 193 In mammalian cells, 2 pathways of tryptophan metabolization have been described. One pathway leads to the L-kynurenine synthesis and thereafter to niacin as the end metabolite.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
See 1 more Smart Citation
“…By inhibiting IDO expression, C. albicans could shift tryptophan metabolism, leading to fewer kynurenines and more 5-hydroxytryptophan metabolites. The increased 5-hydroxytryptophan levels subsequently inhibit host IL-17 production (20).…”
Section: Evasion Of Candida From the Host Defense Mechanismsmentioning
confidence: 99%
“…Although most reports document pathogen sensitivity to tryptophan depletion, recent studies are finding a role for IDO activity in chronic or persistent disease. In particular, IDOtryptophan-directed immunosuppression is thought to play a role in infections by Leishmania major (90), human immunodeficiency virus (reviewed in reference 91), hepatitis C virus (92,93), human papillomavirus (94), Listeria monocytogenes (95), Mycobacterium tuberculosis (96), Candida albicans (97), and Aspergillus fumigatus (98). Importantly, a recent study investigating the role IDO plays in infections by two protozoal species, T. gondii and L. major, found that IDO facilitates T. gondii clearance and suppresses L. major clearance, highlighting the opposing and pathogen-specific roles that IDO can have in infectious disease (90).…”
Section: Pathogen Defence Via Ido (Indoleamine 23-dioxygenase)-mediamentioning
confidence: 99%